Podłoże genetyczne dziedzicznych zaników nerwów wzrokowych - Wawrocka, Anna; R. Krawczyński, Maciej (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
The most common forms of optic atrophy are: autosomatic dominant optic atrophy (ADOA, Kjer type) and maternally-inherited Leber’s hereditary optic neuropathy. Rare forms of hereditary optic neuropathies are: optic atrophy X-linked and autosomatic recessive form of optic atrophy. Autosomatic dominant optic atrophy (ADOA) is the most frequent hereditary optic europathy. Three loci have been reported for ADOA, a major locus maps to 3q28-q29 (OPA1). The majority of mutations responsible for autosomatic dominant optic atrophy are localized in OPA1 gene. Second locus is linked to 18q12.2-q12.3 (OPA4) and a third locus on 22q12.1-q13.1 (OPA5). This study presents the actual state of knowledge about molecular changes in different forms of optic atrophy and shows hypothesis indicating the significant participation of mitochondrial dysfunction in it’s pathogenesis.